Incorporating Religious Moderation Values into Effective English Language Teaching Practices - Nor, Hidayah; Asfihana, Raida; Sari, Afifah Linda; Mahardika, Fadia (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2024)
This research introduces a practical and innovative model for integrating religious moderation values into English Language Teaching activities. Recognizing the multicultural and diverse nature of language learners, this model aims to bridge the gap between language instruction and the incorporation of religious perspectives, fostering a more inclusive and culturally sensitive language learning environment. Phenomenological research used by the researchers as a research design. Grounded in the principles of CLT, the proposed model provides a framework for designing activities for teaching English that seamlessly integrate religious values, encouraging learners to engage in meaningful and contextually relevant language use. The findings showed that the English lecturers have already instilled the values of religious moderation using various ways. The model of lesson plans highlights the significance of including essential social themes like radicalism and tolerance into English lessons plans for university students. It is conducted by employing various multimedia resources, collaborative activities, and reflective assignments to foster dynamic and interactive learning environments that not only increase language proficiency but also encourage critical thinking skills and cultural sensitivity.